Shifting S&T policy paradigm: an experience of an RTO in Thailand. (27th June 2008) - Intarakumnerd, Patarapong; Chairatana, Pun-Arj
This paper portrays an attempt of a Research and Technology Organisation (RTO) in a latecomer country, Thailand, in changing its own strategic direction from a dominant 'knowledge creator' to a 'knowledge broker' in an industrial cluster. A positive transformation in a national innovation system, in which an RTO is operating, can facilitate and even pressure an RTO to change. An RTO itself also has to make a considerable effort to break away from their path dependency. 'Learning by forgetting' is as important as 'learning to accumulate' new competencies, otherwise the existing 'core competencies' can turn to be 'core rigidities'.